2016
DOI: 10.1556/650.2016.30543
|View full text |Cite
|
Sign up to set email alerts
|

Nem konvencionális gyógymódok használata sebészeti betegek között

Abstract: MTA-NAP B Molekuláris Neuroendokrinológiai kutatócsoport, PécsBevezetés: A nem konvencionális gyógymódok egyre emelkedő használata miatt tudnunk kell ezek igénybevételéről a perioperatív ellátás során is. Célkitűzés: A szerzők felmérték az elektív műtétre váró betegek viszonyulását a termé-szetgyógyászati módszerekhez, valamint ezek esetleges igénybevételét és az ezt befolyásoló tényezőket. Módszer: Anonim, kérdőíves felmérést végeztek a Semmelweis Egyetem, I. Sebészeti Klinikán 2014. július és 2016. április k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(16 citation statements)
references
References 24 publications
1
14
1
Order By: Relevance
“… 2 15 21 22 Soós et al found an even lower rate of 20% in surgical patients. 17 In our study, just a few patients told their attending surgeons about CAM, often because they thought that there is no time for it. Whether this is a safety risk or not can, to the present knowledge, only be speculated, because reliable data on the risk of non-communicated CAM are lacking.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“… 2 15 21 22 Soós et al found an even lower rate of 20% in surgical patients. 17 In our study, just a few patients told their attending surgeons about CAM, often because they thought that there is no time for it. Whether this is a safety risk or not can, to the present knowledge, only be speculated, because reliable data on the risk of non-communicated CAM are lacking.…”
Section: Discussionmentioning
confidence: 93%
“…18 Soós et al found a current CAM usage rate of patients underwent surgery at the Department of Surgery of the Semmelweis University, Hungary of 27%, whereof higher rates were observed in patients with cancer. 17 An American survey showed a current CAM usage rate of 25% in surgical patients. 19 Summing up, it appears that nearly a third of surgical patients use CAM even during surgical treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Previous publications were focused on the herb consumption of patients waiting for elective surgery [19] and the attitude of surgery patients towards CAM [20]. In the near future, we are going to survey the attitude towards CAM of healthcare professionals working in perioperative care as well.…”
Section: Methodsmentioning
confidence: 99%
“…Herbal preparations can be a safety hazard in everyday clinical practice, as they are often taken by patients without consulting a physician (1,3). Some substances, such as St. John's wort, have a significant interaction risk (22,23).…”
Section: Risks Of Naturopathic Treatment and Complementary Medicinementioning
confidence: 99%